UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM PENINGKATAN KARAKTER RELIGIUS SISWA SMK NEGERI 5 MALANG - Muhammad Khalim Suryana; Abdul Jalil; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The efforts of Islamic religious education teachers have a very influential role in improving the religious character of students, therefore teachers do not only learn in learning but also in improving the religious character of students. Teachers are needed so that in conveying or instilling a good understanding of students, the religious values accepted by students and carried out well in their daily lives and students are aware that the position of religious education makes them believe and fear God Allah SWT. Based on that, the researchers conducted research at Vocational High School 5 Malang with the title The Efforts of Islamic Religious Education Teachers in Enhancement of Religious Character of Vocational High School 5 Malang Students. Kata Kunci: enhancement of religious character, teachers